Care for major health problems and population health concerns impacts on patients, providers and policy - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2008)
This volume contains papers dealing with macro-level system issues and micro-level issues involving provision of health care as related to major health problems or population health concerns. In the first chapter, the topic of population health is reviewed and examined, looking at relationships between social structure, including socioeconomic status, and health. A number of papers examine social, demographic and structural problems, and a wide variety of major health problems including chronic illnesses, mental illness, serious acute health problems, and disabilities that require health care. Some of the specific health problems covered include major chronic health problems such as coronary heart diseases and arthritis, as well as HIV/AIDs and other sexually transmitted diseases, obesity and how to deal with obesity, mental health concerns, poverty, homelessness and health care problems with a focus on urban contexts within the United States.The last two papers in the volume extend the focus to look at more international concerns. One paper focuses on urban slum prevalence as a key factor in shaping population level rates of social well being in developing countries, and another on medical tourism. This volume includes papers that focus on the perspectives of patients, providers, and also the relevant links with health policy.